The strategically ambiguous assignment: an approach to promoting critical and creative thinking in visual communication. Issue 4 (2nd October 2019) - Bratslavsky, Lauren; Wright, Anna; Kritselis, Alex; Luftig, David
Abstract: This study begins with the assumption that visual and related literacies are essential frameworks to foster not only students' learning of visual communication principles, but also 21st century skills such as creative problem solving and self-directed learning. We focus on assignment directions as a particular instructional component. In contrast to step-by-step directions, strategically ambiguous assignments prompt students to determine the best solutions and course of actions that meet project criteria and suit their abilities. Using a thematic analysis, we analysed student reflections to inquire how students felt about these differences and how students articulated their creative process. In both cases, students learned essential components of visual communication. Notably, the strategically ambiguous assignment prompted students to be more aware of how messages are constructed and take greater pride in their work whereas the clear directions prompted more reflection about the technicalities of working with software.